2016
DOI: 10.1017/s1751731116001038
|View full text |Cite
|
Sign up to set email alerts
|

Coarser wool is not a necessary consequence of sheep aging: allometric relationship between fibre diameter and fleece-free liveweight of Saxon Merino sheep

Abstract: The mean fibre diameter (MFD) of wool is the primary determinant of price, processing performance and textile quality. This study determines the primary influences on MFD as Saxon Merino sheep age, by allometrically relating MFD to fleece-free liveweight (FFLwt). In total, 79 sheep were grazed in combinations of three stocking rates and two grazing systems (GS: sheep only; mixed with Angora goats) and studied over 3 years. Measurements were made over 14 consecutive periods (Segments), including segments of FFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…In Karacabey Merino sheep, Atav et al [9] reported that the mean of wool diameter as 28.67 µm which is higher than our result. However, the study conducted on Saxon Merino sheep and Anatolian Merino sheep (i.e., Central Anatolian Merino), the fibre diameters were found respectively, as 18.8 µm and 20.08 µm which is significantly lower than our study [37,38].…”
Section: Fibre Diametercontrasting
confidence: 89%
“…In Karacabey Merino sheep, Atav et al [9] reported that the mean of wool diameter as 28.67 µm which is higher than our result. However, the study conducted on Saxon Merino sheep and Anatolian Merino sheep (i.e., Central Anatolian Merino), the fibre diameters were found respectively, as 18.8 µm and 20.08 µm which is significantly lower than our study [37,38].…”
Section: Fibre Diametercontrasting
confidence: 89%
“…Adult ewe wool traits are key determinants of Merino flock income [38,39]. Wool micron accounts for 80% of the fleece value, with finer wool obtaining the highest prices [40][41][42]. During the FMP period (1999-2010), ewe FD decreased by approximately 3 µm, from 19 to 16 µm, which is comparable with previously reported reductions in FD in yearling lambs of the same flock [24].…”
Section: Discussionsupporting
confidence: 68%
“…A possible explanation for this result could be that the adopted supplementation was too late in the gestational moment, decreasing the effect on the overall parameters studied. However, McGregor and Butler (2016) showed that the diameter of fibre wool in Merino is an allometric property and that it is affected by the live weight of the sheep. Consequently, it is highly probable that as the live weight and the live weight gain of lambs with different treatments was the same over the first year of life, a difference in the diameter of fibre wool could not be expected.…”
Section: Resultsmentioning
confidence: 99%